Natural Resource Booms and Inequality: Theory and Evidence. - Goderis, B; Malone, S (OxCarre, 2008)
Surprisingly little is known about the impact of resource booms on income inequal- ity in resource rich countries (Ross, 2007). This paper develops a simple theory, in the context of a two sector growth model in which learning-by-doing drives growth, to explain the time path of inequality following a resource boom. Under plausible con- ditions, we …nd that income inequality will fall in the short run immediately after a boom, and will then increase steadily over time as the economy grows, until the initial impact of the boom on inequality disappears. Using panel cointegration methodology for a sample of 90 countries between 1965 and 1999, we test the predictions of the model empirically. We …nd strong evidence in support of the theory. Resource booms, especially mineral booms, lower inequality in the year of the boom. This e¤ect then gradually diminishes over time until inequality returns to its pre-boom level in the long run.